DFIS: A novel data filling approach for an incomplete soft set - Qin, Hongwu; Ma, Xiuqin; Herawan, Tutut; Zain, Jasni Mohamad (Zielona Góra: Uniwersytet Zielonogórski)
The research on incomplete soft sets is an integral part of the research on soft sets and has been initiated recently. However, the existing approach for dealing with incomplete soft sets is only applicable to decision making and has low forecasting accuracy. In order to solve these problems, in this paper we propose a novel data filling approach for incomplete soft sets.
Keywords: soft sets; incomplete soft sets; data filling; association degree